Effects and mechanisms of acupuncture analgesia mediated by afferent nerves in acupoint microenvironments - Fan, Zezhi; Dou, Baomin; Wang, Jiangshan; Wu, Yongjian; Du, Simin; Li, Jiashan; Yao, Kaifang; Li, Yanwei; Wang, Shenjun; Gong, Yinan; Guo, Yi; Xu, Zhifang (Frontiers in Neuroscience, 2024)
In the past few decades, acupuncture analgesia has increasingly been applied in clinical practice. It has several advantages including endogenous reduction of patients' pain levels and the ability to avoid several Non-steroidal anti-inflammatory drugs (NSAID) and opioid-associated adverse effects. Acupuncture stimulates acupoints which rapidly and directly induces activation of high-density primary afferent fibers under the acupoints, including myelinated A fibers and unmyelinated C fibers. During acupuncture stimulation at the muscle layer, the analgesic effects can be induced by stimulation of the A fiber threshold intensity. At the skin layer, the analgesic effects can only be produced by stimulation of C fiber threshold intensity. Electroacupuncture (EA) with low stimulation activates A fibers, while manual acupuncture (MA) with high stimulation activates both A and C fibers. Acupuncture leads causes changes in acupoint microenvironments, which positively modulates afferent fibers, enhancing the transmission of analgesic signals. In the spinal cord, acupuncture activates neurons by inducing afferent fiber depolarization, modulating pain gating, inhibiting long-term potentiation (LTP) of the spinal dorsal horn and wide dynamic range (WDR) neuronal activities. At higher nerve centers, acupuncture inhibits neuronal activation in pain-related brain regions. In summary, acupuncture inhibits pain signal transmission at peripheral and central systems by activating different patterns of afferent fibers located on various layers of acupoints. Therefore, exploring its action patterns and mechanisms will reveal ideas that enhance the precise application and clinical translation of acupuncture.